Wattpad User Satisfaction Analysis Using System Usability Scale (SUS) Method - Prita Dellia; Ayu Pratiwi; Nawafilillah; Tania Adela Sapitri; Annis Izzaturrahmah (Kresnamedia Publisher, 2025)
Wattpad is an app that you can use to read, write, share, and comment on stories from various genres, such as romance, horror, fantasy, and more. This app is in high demand, especially by young people, because of its ease of use and provides many interesting stories for free. In this study, the author wants to find out how easy and convenient the Wattpad application is to be used by its users. For this reason, the System Usability Scale (SUS) method is used, which is a measurement tool commonly used to assess the usability of a system or application. Researchers collected data by distributing a questionnaire via Google Forms to 50 people who used Wattpad. The results of the questionnaire showed that the average SUS score obtained was 72.2. This value is included in the